PENGARUH PEMBELAJARAN KEWIRAUSAHAAN, PENGETAHUAN KEWIRAUSAHAAN, PENGALAMAN PRAKTEK KERJA INDUSTRI, DAN LINGKUNGAN KELUARGA TERHADAP MINAT BERWIRAUSAHA DENGAN EFIKASI DIRI SEBAGAI VARIABEL INTERVENING PADA SISWA SMK NEGERI DI KOTA MAKASSAR - Sumiati Tahir (SEMINAR NASIONAL DIES NATALIS 62, 2023)
The Effect of Entrepreneurship Learning, Entrepreneurial Knowledge, Industrial Work Practice Experience, and Family Environment on Entrepreneurial Interest with Self-Efficacy as An Intervening Variable in State Vocational High Students in Makassar. This study aims to determine the effect of entrepreneurship learning, entrepreneurship knowledge, and industrial work practice experience and family environment on entrepreneurial interest either directly or indirectly through self-efficacy as an intervening variable. The population in this study was 3530 students of class XII State Vocational High Students in Makassar and a sample of 845 students slovin formula with a standard error of 3% applying Cluster Random Sampling method. The data collection method used is a questionnaire. Data analysis is done through descriptive analysis, path analysis, and sobel test using SPSS and Smart PLS software. The results showed that 1) directly, there is a positive and significant effect of entrepreneurship learning, entrepreneurial knowledge and family environment on self-efficacy 2) directly, there is a positive and significant effect of entrepreneurship learning, entrepreneurial knowledge, self-efficacy and on entrepreneurial interest, 3) indirectly, there is a positive and significant effect of entrepreneurship learning, entrepreneurial knowledge and family environment on entrepreneurial interest through self-efficacy. However, industrial work practice experience is found not significant on self-efficacy and entrepreneurial interest of vocational students.